The Understanding of The Effectiveness of Digitizing Economic Management In Profitable and Sustainable Small Business Development Practices - Jacob, Jufri; Purbaningsih, Yuli; Sembiring, H. MR. Ulung; Ng, Suwandi; Septo Pramesworo, Ignatius (Jurnal Mamangan, 2023)
The importance of understanding digital-based economic governance to achieve effectiveness in implementing profitable and sustainable small business development is essential to research. The author sees that only a few technology-based minor business development themes have shown the effectiveness of economic governance with the help of technology. We searched our data electronically in several journals, which included several publications, including Emerald Group Publishing, Elsevier publication, Pearson, UK, Willy online library, Taylors & Francis publications, Springers publications, IEEE publications, and several publications that discuss issues of economic development based on technology. After a series of data analyses involving several data analysis techniques under a phenomenological approach, we can finally conclude that the effectiveness of digital-based economic governance is an essential strategy and approach in developing a sustainable and profitable small business enterprise. The reason is that technology with innovative capabilities and transformation can provide convenience for business implementers to run their businesses effectively and efficiently toward being productive.